An Iron(II) Chloride‐Promoted Radical Cascade Methylation or α‐Chloro‐β‐methylation of N‐Arylacrylamides with Dimethyl Sulfoxide. Issue 2 (4th January 2017) - Li, Zejiang; Cui, Xiaosong; Niu, Lin; Ren, Yingming; Bian, Menghua; Yang, Xuebiao; Yang, Biao; Yan, Qinqin; Zhao, Jincan
Abstract: A free radical‐initiated methylation and/or α‐chloro‐β‐methylation of N ‐arylacrylamides with dimethyl sulfoxide under the analogous Fenton reaction condition has been developed, which provides an effective and facile cascade strategy for the synthesis of oxindoles and chlorinated amides. Abstract :